2018
DOI: 10.1186/s12940-018-0408-8
|View full text |Cite
|
Sign up to set email alerts
|

Deepwater Horizon oil spill exposures and nonfatal myocardial infarction in the GuLF STUDY

Abstract: BackgroundWorkers involved in the response and clean-up of the 2010 Deepwater Horizon oil spill faced possible exposures to crude oil, burning oil, dispersants and other pollutants in addition to physical and emotional stress. These exposures may have increased risk of myocardial infarction (MI) among oil spill workers.MethodsGulf Long-term Follow-up (GuLF) STUDY participants comprise individuals who either participated in the Deepwater Horizon response efforts or registered for safety training but were not hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
13
1
2
Order By: Relevance
“…In a non-WTC study of the aftermath of an oil spill, those who worked on the cleanup for more than 180 days—similar to our duration exposure measure—showed a significantly greater long-term incidence of heart disease. 37…”
Section: Discussionmentioning
confidence: 99%
“…In a non-WTC study of the aftermath of an oil spill, those who worked on the cleanup for more than 180 days—similar to our duration exposure measure—showed a significantly greater long-term incidence of heart disease. 37…”
Section: Discussionmentioning
confidence: 99%
“…Further, exposure to the DWHOS was a predictor of higher rates of poor mental health in the same cohort of women [62]. The Gulf Long-term Follow-up (GuLF) Study, a cohort study following the health of DWHOS clean-up workers and volunteers, found that working on the spill for more than 180 days and stopping work due to heat exposure were associated with a greater risk of nonfatal myocardial infarction (i.e., heart attack) [63]. The GuLF study also found high amounts of total hydrocarbon exposure or stress on the job were associated with an increased prevalence of depression and PTSD [64].…”
Section: Health Impacts Of Pollutants In Galveston Baymentioning
confidence: 99%
“…Lyons et al, 1999;Janjua et al, 2006;Zock et al, 2007;Peres et al, 2016 Irritação na pele e nas mucosas (nariz e olhos). Strelitz et al, 2018 Aumento de risco de infarto do miocárdio em trabalhadores expostos por mais de 180 dias. Gill;Picou 1998;Nriagu et al, 2016;Rung et al, 2016 Aumento dos níveis de estresse.…”
Section: Rotkin-ellman Et Al 2012;unclassified
“…Um estudo feito por Strelitz et al (2018) sobre o desastre de Deepwater Horizon mostrou aumento expressivo de infarto do miocárdio em indivíduos que trabalharam na limpeza do óleo e/ou moravam nas proximidades de onde ocorreu o derramamento. Os autores sugerem que mais estudos sejam feitos para definir se esse aumento é devido à exposição a compostos contaminantes propriamente ditos, se é pelo aumento do estresse causado pelo calor ou por uma associação de ambos os fatores.…”
Section: Psicológicosunclassified